2020
DOI: 10.1111/joor.12948
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sarcopenia and oral sarcopenia in elderly people

Abstract: In the ageing society, sarcopenia, in which muscle strength and motor function decline with age, has attracted attention, and many researchers have investigated different testing and treatment methods. 1-6 Aspiration resulting from reduced swallowing function is a problem in the elderly, and aspiration pneumonia significantly deteriorates the life prognosis and QOL. 7 These disorders associated with reduced swallowing function were dysphagia. As sarcopenia is involved in the onset of dysphagia, 8,9 the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
52
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 31 publications
9
52
0
5
Order By: Relevance
“…A decrease in MTP correlated with a decrease in SMI, supporting the results of Kobuchi et al 31 PPWA was not associated with SMI. This result is at odds with the finding that MTP was significantly associated with SMI.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A decrease in MTP correlated with a decrease in SMI, supporting the results of Kobuchi et al 31 PPWA was not associated with SMI. This result is at odds with the finding that MTP was significantly associated with SMI.…”
Section: Discussionsupporting
confidence: 88%
“…Result of multiple regression analysisreasons that the tongue pressure and the amount of laryngeal elevation were related.A decrease in MTP correlated with a decrease in SMI, supporting the results of Kobuchi et al31 PPWA was not associated with SMI. This result is at odds with the finding that MTP was significantly associated with SMI.…”
supporting
confidence: 88%
“…All TP values measured using the JMS are in the Japanese studies. [2][3][4]7,14,16,20,[22][23][24]33,35,37,38,41,42,44,46,47,49,51,[55][56][57][59][60][61]64,[73][74][75][76][77][78][79][80][81][82][83] It has been considered that TP values measured using the IOPI are slightly higher in the Chinese study 69 than in the European studies, 15,72 slightly lower than in the US studies, 17,34 and close to those in Korean study. 52 It is supposed that these differences among regions are caused by physical constitution such as height, weight or overall muscle mass, and chewing frequency, duration or patterns 52 as well as eating habits.…”
Section: F I G U R E 2 (Continued)mentioning
confidence: 99%
“…7,74 Only a single study reported on the association between TP and cognitive function 75. For future studies, measuring TP in cohorts with different levels of cognitive and/or physical function would add further information of its influence on TP.…”
mentioning
confidence: 99%
“…Oral frailty-the accumulation of a slightly poor status in oral conditions and function-strongly predicted physical frailty, dysphagia, malnutrition, the need for long-term care, and mortality in community-dwelling older adults (4). Oral sarcopenia refers to sarcopenia associated with oral conditions and function, but its definition has not yet been fully discussed (2,6,24). These age-related concepts of «oral decline» are clinically relevant in rehabilitation settings because they represent a precursor to functional impairment, although more research is needed to determine their definitions and diagnoses.…”
Section: Agingmentioning
confidence: 99%